Early Childhood Caries Prevalence and Relationship with Risk Factors - Nafisa, Alia; Syafriza, Dharli; Rifki, Ayudia (Cakradonya Dental Journal, 2025)
Early Childhood Caries (ECC) is a disease of the hard tissues of the teeth in children under 5 year of age. In addition to the main etiological factors, there are several supporting factors that contribute to the occurrence of ECC, including exclusive breastfeeding, socioeconomic status, dietary patterns and habits of children, and oral hygiene behavior of children. The prevalence rate of ECC in Indonesia is still relatively high, with varying prevalence rates and no recent data on ECC prevalence in Banda Aceh. The purpose of this study is to determine the prevalence of ECC in early childhood and its risk factors. This study is analytical in nature, using a cross-sectional design on children aged 4-6 years who attend the kindergarden in Banda Aceh. A total of 123 children met the inclusion criteria. Data collection was obtained through direct clinical examination of the oral cavity using Debris Index measurements and ECC typing. The results of this study showed that the prevalence of ECC reached 87,1%, and factors such as birth weight, frequency of brushing teeth daily, consumption of milk with a bottle, brushing teeth accompanied by parents, and frequency of consuming sweet foods as snacks were significant factors in the occurrence of ECC.